A brief illustrated guide to understanding Islam I.A. Ibrahim ; general editors, William (Daoud) Peachy, Michael (Abdul Hakim) Thomas, Tony (Abu-Khaliyl) Sylvester, Idris Palmer, Jamaal Zarabozo, Ali AlTimimi ; science editors , Harold Stewart Kuofi, F.A State, Mahjoub O. Taha, Ahmad Allam, Salman Sultan, H.O Sindi - Ibrahim, I.A (Darussalam, 1997)
This book is a brief guide to understanding Islam. It consists of three chapters, "Chapter 1: Some evidence for the truth of Islam", "Chapter 2: Some benefits of Islam " and "Chapter 3: General information on Islam"